An RCT of acute health effects in COPD-patients after passive vape exposure from e-cigarettes. Issue 1 (1st January 2021) - Rosenkilde Laursen, Karin; Bønløkke, Jakob Hjort; Bendstrup, Elisabeth; Bilde, Merete; Glasius, Marianne; Heitmann Gutzke, Vibeke; Puthukkadan Moosakutty, Shamjad; Olin, Anna-Carin; Ravn, Peter; Østergaard, Kirsten; Sigsgaard, Torben
ABSTRACT: Background : E-cigarette use has been shown to have short-term acute effects among active users but less is known of the acute passive effects, particularly among individuals with existing respiratory diseases. Objective : To investigate local and systemic effects of short-term passive vape exposure among patients with mild or moderate chronic obstructive pulmonary disease (COPD). Methods : In a double-blinded crossover study 16 non-smoking COPD-patients (mean age 68) were randomly exposed for 4 h to passive vape (median PM2.5 : 18 µg/m 3 (range: 8–333)) and clean air (PM2.5  < 6 µg/m 3 ) separated by 14 days. Particles were measured using an ultrafine particle counter (P-TRAK) and a scanning mobility particle sizer (SMPS). Health effects including Surfactant Protein-A (SP-A) and albumin in exhaled air, spirometry, FeNO, and plasma proteins were evaluated before, right after, and 24 hours after exposure. Participants reported symptoms throughout exposure sessions. Data were analyzed using mixed models. Results : SP-A in exhaled air was negatively affected by exposure to vape and several plasma proteins increased significantly. Throat irritation was more pronounced during passive vape exposure, while FVC and FEV1 decreased, however, not significantly. Conclusions: SP-A in exhaled air and some plasma proteins were affected by passive vape in patients with COPD indicating inflammation, showing that passive vape exposure is potentially harmful.